Long-term Functional Outcomes and Complications in Operative Versus Nonoperative Treatment for Displaced Midshaft Clavicle Fractures in Adolescents: A Retrospective Comparative Study. Issue 5 (May 2021) - Riiser, Martin O.; Molund, Marius
Abstract : Introduction: Traditionally, midshaft clavicular fractures in adolescents are treated nonoperatively. In later years, a trend toward operative treatment can be observed. Documentation of the benefit of surgery in this group is scarce. The purpose of this study is to evaluate the long-term patient reported functional outcomes and complications for patients treated operatively and nonoperatively for displaced midshaft clavicular fractures. Using the same outcomes we also compared the operative methods. Methods: One hundred nine adolescents aged 12 to 18 years sustaining displaced midshaft clavicular fractures in the period 2010 to 2016 were identified in our computerized files. Sixty-one were treated nonoperatively, 48 operatively (22 plate and 26 intramedullary nail). Their radiographs and patient journals were examined for fracture classification, wound infection, sensory affection, surgery duration, hardware removal, and nonunion (n=109). Long-term function, pain, and satisfaction were measured with Quick Disability of Arm, Shoulder, and Hand (QuickDASH), Oxford Shoulder Score and Visual Analogue Scale (n=87). Results: Operative treatment: We could find no difference in functional score outcomes. The main outcome QuickDASH was excellent in both groups (median 0 nail vs. 2.26 plate). Surgery duration was shorter with intramedullary nail. We found 2 infections and 2 sensory affections in the plate group, and 1 infection and 1 sensory affection in the intramedullary nail group. There were 2 refractures in the nail group. Operative versus nonoperative treatment: there were no differences in functional outcomes between the operative and nonoperative groups. For the main outcome QuickDASH both groups scored excellently (median 1.12 operative vs. 0 nonoperative). The nonoperative group was more satisfied with the cosmetic result. There was 1 nonunion in the nonoperative group that later was operated. Conclusions: Adolescents aged 12 to 18 years with displaced midshaft clavicular fractures show good long-term functional results after plate fixation, intramedullary nail, and nonoperative treatment. No additional benefit is demonstrated for surgery in our material. Nonoperatively treated patients are more satisfied with the cosmetic results. Little difference is seen between the operative methods in our study. We conclude that surgery should rarely be the choice of treatment for displaced midshaft clavicular fractures in adolescents. Level of Evidence: Level III study—retrospective comparative study.